The Degradation Characteristics of Feed Supplemented Gliricidia Leaves in Goat Rumen in sacco - D. R. Zulkarnain; . Ismartoyo; . Harfiah (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2014)
This research was aimed to determine the degradation characteristics of dry matter (DM) and organic matter (OM) of three different forages enriched with gliricidia leaves (GL). The forages used in this trial were mini elephant grass (MEG), kolonjono grass (KG), and field grass (FG). Data collected were the nutrient digestibility of forage residues in the rumen, i.e. DM and OM. Samples were incubated in the rumen of fistulated goat at different interval times, i.e. 8, 12, 24, 48, 72 and 96 hours. The experiment was carried out according to completely randomized design (CRD) consisted of 3 treatments and 3 replications, MEG 75% + 25% GL (T1), KG 75% + 25% GL (T2), and FG 75% + 25% GL (T3). The results showed that the treatments affected (P<0.05) the values of a, b and c fraction for T1, T2, and T3. DM degradation characteristics of the T1 values were 23.2%, 25.62%, and 3%/h, respectively for a, b, and c fractions. The values for treatment T2 were 3.3%, 35.10%, and 5%/h, and the values for T3 were 11.8%, 46.62%, and 1%/h, respectively for a, b and c fractions. OM degradation characteristics of the T1 were 23.2%, 43.38%, and 1%/h, respectively for fractions a, b and c, while the degradation values for OM of T2 were 23.3%, 36.78% and 4%/h, and the values of treatment T3 were 11.8%, 31.29%, and 1%/h, respectively for a, b, and c fractions. Among the forages, the most rapidly degraded was T2, followed by T1 and T3.